Pelanggaran Hak Kekebalan Terhadap Gedung Perwakilan Diplomatik - Ni Putu Era Daniati (Universitas Pendidikan Ganesha, 2020)
Violation of the rights and immunity of a diplomat is a violation of International Law. The occurrence of violations committed by diplomatic officials is due to misuse of duties and authority carried out by diplomatic officials themselves. Immunity and diplomatic privileges are rooted in international law so that those who have the right to give and take it off are subject to international law. Immune dating can only be carried out by the sending country which is the agency that is authorized to abandon the duties of the diplomatic official himself. Immunity and privilege of diplomatic officials do not have to be done by the head of the recipient country.